2017
DOI: 10.1144/sp454.1
|View full text |Cite
|
Sign up to set email alerts
|

Determining the porosity of mudrocks using methodological pluralism

Abstract: Porosity of shales is an important parameter that impacts rock strength for seal or wellbore integrity, gas-in-place calculations for unconventional resources or the diffusional solute and gas transport in these microporous materials. From a well section obtained from the Mont Terri Underground Rock Laboratory in St Ursanne, Switzerland, we determined porosity, pore size distribution and specific surface areas on a set of 13 Opalinus Clay samples. The porosity methods employed are helium-pycnometry, water and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(73 citation statements)
references
References 57 publications
2
71
0
Order By: Relevance
“…All VSANS measurements were conducted at the KWS‐3 instrument at JCNS (Pipich & Zhendong, ). Results for Opalinus Shale have been reported earlier (Busch et al, ). With the exception of one Boom Clay sample (K4), all samples were cut parallel to bedding, fixed on quartz glass carriers, and polished to a thickness of about 200 m. Samples were dried at room temperature, and measurements were performed under ambient pressure and temperature conditions.…”
Section: Methodssupporting
confidence: 75%
See 4 more Smart Citations
“…All VSANS measurements were conducted at the KWS‐3 instrument at JCNS (Pipich & Zhendong, ). Results for Opalinus Shale have been reported earlier (Busch et al, ). With the exception of one Boom Clay sample (K4), all samples were cut parallel to bedding, fixed on quartz glass carriers, and polished to a thickness of about 200 m. Samples were dried at room temperature, and measurements were performed under ambient pressure and temperature conditions.…”
Section: Methodssupporting
confidence: 75%
“…Pores can be spherical, slit‐shaped, or ellipsoidal or have more complex geometries, as has been shown in previous studies (Desbois et al, ; Leu et al, ; Loucks et al, ). We have used the spherical model in a previous study on Opalinus Shale and demonstrated that porosity calculations originating from this approach match porosity determinations using Helium pycnometry or water porosimetry (Busch et al, ). Furthermore, using a different approach (e.g., ellipsoid pores) would not have an impact on the fractal dimension or the slope of the scattering intensity versus pore radius and we are therefore confident that the approach used in this study is suitable.…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations